THE EDUCATION OF STUDENTS WITH AUTISM SPECTRUM DISORERS FROM THE TEACHER ` S VIEWPOINT – A CZECH / POLISH COMPARATIVE STUDY AT THE SECONDARY EDUCATION LEVEL - Urbanovská, Eva; Kantor, Jiří; Růžička, Michal (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
ASD are a widely discussed and topical area in the forefront of the interest of professionals from a number of scientific fields. The following paper approaches the issue from the viewpoint of special education and focuses on the area of educating students with autism spectrum disorders at the secondary education level. The topic was addressed under a quantitative investigation undertaken at Czech and Polish schools. The paper presents a part of the results obtained from the investigation. We focus special attention to the issue of raising awareness on the part of secondary school teachers. Further factors will be outlined, such as: factors determining instruction, factors evaluated as the most demanding by teachers while working with students with ASD and action proposed to optimise vocational training of students with ASD.